In situ fabrication of cellular architecture on silver metals using methane/oxygen gas mixture and its application for energy storage. (1st August 2018) - Cao, Fenghui; Wang, Zhihong; Wang, Yuzhi; Yan, Yingming; Liu, Mengting; Li, Lang; Ao, Guanghong; Chen, Kongfa; Lv, Zhe
Abstract: Cellular metals with a large surface-to-volume ratio and excellent electrical conductivity have attracted great attention due to their wide application. However, the existing processes for fabrication of cellular metallic structures are generally complex and dependent on the sacrificial materials or templates, and therefore, it is highly desirable to develop a facile process. Herein, we propose a novel gas-assisted reconstruction strategy for in situ fabrication of micron-porous architectures on Ag precursor metal using a CH4 /O2 gas mixture at 750 °C. The obtained results indicate that large-area and clean, porous Ag architectures are successfully created through the treatment in CH4 /O2 gas. The formation of cellular structure is mainly due to the simultaneous diffusion of H2, CO and O2 into Ag bulk and fast reaction at elevated temperatures. The process is clean and applicable to creation of porous architectures (from surface texturing to 3-D cellular structure) on Ag metal, avoiding the use of sacrificial materials or templates. Furthermore, we have demonstrated that the formed micron-porous Ag sheet with large effective area, high electrical conductivity can be directly used as a free-standing electrode for electrochemical supercapacitors with a high capacitance. Graphical abstract: Highlights: A micron-porous cellular structure on silver metal was created in CH4 /O2 mixture. This process is clean, avoiding the use of sacrificial materials or templates. The process could create porous structures from surface to 3D cellular structure. The formed MPAS displays high capacity and excellent cycling stability. The strategy is applicable to micron-porous structure of other Ag-alloy systems.